Negative active material, preparation method thereof and battery

By using the combined material of metal nanoparticles and porous carbon in lithium ion batteries, carbon nanotubes and carbon coating layers are formed through multiple carbon sources and silicon source sedimentation treatment. The problem of shedding the material caused by silicon expansion achieves high ratio and good cycle stability.

CN119381421APending Publication Date: 2025-01-28NINGBO YINGCHUANG SCI & TECH ACHIEVEMENTS TRANSFORMATION SERVICE PARTNERSHIP (LLP)
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411314333.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, graphite, as the negative electrode active material, has reached the theoretical limit and is difficult to further improve. Moreover, the silicon-carbon negative electrode active material has caused material shedding and structural damage due to silicon expansion during circulation.

Method used

By mixing metal nanoparticles and porous carbon, multiple carbon sources and silicon source deposition treatment are performed to form a carbon nanotuba coverage layer and carbon coating layer, limiting the growth and volume expansion of silicon single, improving the mechanical strength and electricity of materials Chemical performance.

Benefits of technology

The high ratio capacity, good circulation stability and high charging and discharge efficiency of negative active materials are realized, and the material density and cycle performance of the battery are alleviated, and the battery energy density and cycle performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381421A_ABST
    Figure CN119381421A_ABST
Patent Text Reader

Abstract

The invention discloses a negative electrode active material, a preparation method thereof and a battery. The method for preparing the negative electrode active material comprises the following steps: mixing metal nanoparticles and porous carbon to obtain a mixture; performing first carbon source deposition treatment on the mixture to obtain a first material; performing silicon source deposition treatment on the first material to obtain a second material; and performing second carbon source deposition treatment on the second material to obtain the negative electrode active material. According to the invention, metal nanoparticles are introduced into pores of porous carbon, and the metal nanoparticles are used as a nucleation center to promote a carbon source to form a network structure of a single-wall or multi-wall carbon nanotube in the pores or on the surface of the porous carbon; the silicon particles are deposited on the surfaces of the carbon nanotubes or in smaller pores of the porous carbon, so that the growth of the silicon particles is limited; and finally, a carbon coating layer with an elastic protection effect and high conductivity is formed on the surface of the porous carbon, so that the problem that the silicon-carbon negative electrode active material falls off due to expansion of silicon particles in the circulation process is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of secondary battery energy storage, and in particular, to negative electrode active materials and preparation methods thereof, and batteries. Background Art

[0002] In the field of lithium-ion batteries, the energy density of graphite as a negative electrode active material has approached the theoretical limit, so there is an urgent need to find negative electrode active materials with higher energy density. Silicon-carbon negative electrode active materials are considered the first choice for the next generation of high energy density negative electrode active materials due to their advantages of high energy density, low charge and discharge platform voltage and high initial coulomb efficiency.

[0003] It should be noted that the above statements are only used to provide background technical information related to the present application and do not necessarily constitute prior art. Summary of the invention

[0004] In a first aspect of the present application, the present application provides a method for preparing a negative electrode active material, comprising: mixing metal nanoparticles and porous carbon to obtain a mixture; performing a first carbon source deposition treatment on the mixture to obtain a first material; performing a silicon source deposition treatment on the first material to obtain a second material; performing a second carbon source deposition treatment on the second material to obtain a negative electrode active material.

[0005] Therefore, the present application introduces metal nanoparticles into the pores of large-aperture porous carbon. In the first carbon deposition process, the metal nanoparticles are used as nucleation centers to promote the carbon source gas to form a network structure of single-walled or multi-walled carbon nanotubes in the pores or on the surface of the porous carbon. The formed carbon nanotube coating not only exhibits high crystallinity and hardness, but also has good electrical conductivity and mechanical properties, while effectively blocking the large pores of the porous carbon, thereby reducing the pore size of the porous carbon; in the subsequent silicon deposition stage, silicon element is deposited on the surface of the carbon nanotubes or in the smaller porous carbon pores, thereby limiting the excessive growth of silicon element; finally, in the second carbon deposition process, a carbon coating layer with elastic protection and high conductivity is formed on the surface of the porous carbon, and the carbon coating layer can not only inhibit the volume expansion of silicon, but also improve the mechanical strength and electrochemical properties of the porous carbon, thereby alleviating the problem of the silicon-carbon negative electrode active material falling off due to silicon expansion during the cycle.

[0006] In some embodiments, the mass of the metal nanoparticles is 0.1%-1% of the mass of the mixture. Thus, the metal nanoparticles can both promote the growth of carbon nanotubes and restrict the growth of silicon, thereby achieving the regulation of the performance of the negative electrode active material.

[0007] In some embodiments, the porous carbon includes at least one of biomass-based porous carbon, resin-based porous carbon, and petroleum asphalt-based porous carbon. Thus, different types of porous carbon have different pore structure characteristics, and porous carbon of suitable materials can provide a variety of growth spaces for the deposition of silicon and carbon nanotubes.

[0008] In some embodiments, the specific surface area of ​​the porous carbon is 500 m 2 / g-1000m 2 / g. Therefore, by selecting porous carbon with a suitable specific surface area, it is possible to provide a suitable growth space for the deposition of silicon and carbon nanotubes while maintaining the stability of the porous carbon structure.

[0009] In some embodiments, the metal nanoparticles include at least one of manganese, iron, cobalt, nickel, copper, and zinc. Thus, selecting metal nanoparticles of suitable materials can promote the decomposition of the carbon source gas during the deposition process and accelerate the growth of carbon nanotubes.

[0010] In some embodiments, the particle size of the metal nanoparticles is less than or equal to 10 nm. Thus, selecting metal nanoparticles with a suitable particle size can provide more active sites for the subsequent catalytic reaction of the carbon source gas, thereby improving the catalytic efficiency.

[0011] In some embodiments, the first carbon source deposition process satisfies at least one of the following conditions:

[0012] The deposition temperature of the first carbon source deposition process is 1000°C-2000°C;

[0013] The carbon source for the first carbon source deposition treatment includes at least one of acetylene, methane, and ethylene;

[0014] The deposition time of the first carbon source deposition treatment is 0.1h-3h;

[0015] The carbon source flow rate of the first carbon source deposition process is 0.1 L / h-0.5 L / h.

[0016] Therefore, selecting appropriate deposition temperature, carbon source, deposition time, and carbon source flow rate is conducive to the decomposition of the carbon source gas and the formation of carbon nanotubes.

[0017] In some embodiments, the silicon source deposition process satisfies at least one of the following conditions:

[0018] The deposition temperature of the silicon source deposition process is 450°C-650°C;

[0019] The silicon source for the silicon source deposition process comprises at least one of silane, disilane, dichlorosilane, tetramethylsilane, and dimethyldichlorosilane;

[0020] The deposition time of the silicon source deposition process is 0.5h-5h;

[0021] The silicon source flow rate of the silicon source deposition process is 0.1 L / h-0.5 L / h.

[0022] Therefore, choosing the appropriate deposition temperature, silicon source, deposition time, and silicon source flow rate will help control the size of the silicon element.

[0023] In some embodiments, the second carbon source deposition process satisfies at least one of the following conditions:

[0024] The deposition temperature of the second carbon source deposition process is 700°C-1000°C;

[0025] The carbon source of the second carbon source deposition treatment includes at least one of acetylene, methane, and ethylene;

[0026] The deposition time of the second carbon source deposition treatment is 0.1h-3h;

[0027] The carbon source flow rate of the second carbon source deposition process is 0.1 L / h-0.5 L / h.

[0028] Therefore, selecting appropriate deposition temperature, carbon source, deposition time, and carbon source flow rate helps to control the coating degree of the carbon coating layer.

[0029] In some embodiments, the temperature of the mixture is raised to the deposition temperature of the first carbon source deposition treatment by the first temperature raising treatment. Thus, the mixture reaches the deposition temperature of the first carbon source deposition treatment in advance, which alleviates the problem of local overheating of the mixture during the first carbon source deposition treatment and provides a suitable growth environment for subsequent carbon nanotube deposition.

[0030] In some embodiments, the first temperature reduction process is performed to reduce the temperature of the first material to the deposition temperature of the silicon source deposition process, thereby providing a suitable growth environment for subsequent silicon single substance deposition.

[0031] In some embodiments, the second temperature raising process is performed to raise the temperature of the second material to the deposition temperature of the second carbon source deposition process, thereby providing a suitable growth environment for subsequent carbon coating layer deposition.

[0032] In some embodiments, the heating rates of the first heating treatment and the second heating treatment are independently 1°C / min-10°C / min, thereby helping to reduce the thermal stress caused by the rapid temperature change of the mixed material or the second material, thereby reducing the risk of porous carbon cracking.

[0033] In some embodiments, the cooling rate of the first cooling treatment is 1°C / min-10°C / min, thereby helping to reduce significant deformation of the first material due to excessively fast cooling, thereby reducing the risk of the first material breaking.

[0034] In a second aspect of the present application, the present application provides a negative electrode active material prepared by the above method. Therefore, the negative electrode active material of the present application has high specific capacity, good cycle stability and high initial charge and discharge efficiency.

[0035] In the third aspect of the present application, the present application provides a battery, comprising a negative electrode sheet, the negative electrode sheet comprising a current collector, and a negative electrode active material layer located on at least one side of the current collector, the negative electrode active material layer comprising a negative electrode active material, the negative electrode active material comprising a negative electrode active material prepared by the aforementioned method, or the aforementioned negative electrode active material. As a result, the battery of the present application has the advantages of high energy density, good cycle stability and good safety, and meets the needs of high-energy, long-life batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0037] Figure 1 It is a schematic diagram of the process flow of negative electrode active materials in one embodiment of the present application.

[0038] Figure 2 It is a first cycle charge and discharge curve diagram of a button cell prepared using the negative electrode active material of Example 4.

[0039] Figure 3 It is a curve diagram of the specific capacity of the button cell prepared by using the negative electrode active material of Example 4 during the first 10 cycles.

[0040] Figure 4 This is a first cycle charge and discharge curve of a button cell prepared using the negative electrode active material of Comparative Example 1.

[0041] Figure 5 This is a curve of the specific capacity of the button battery prepared using the negative electrode active material of Comparative Example 1 during the first 10 cycles. DETAILED DESCRIPTION

[0042] Hereinafter, the negative electrode active material and its preparation method, and the battery implementation mode of the present application are specifically disclosed with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0043] " Scope " disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be to include end values ​​or not include end values, and can be combined arbitrarily, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 listed, and if the maximum range values ​​3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0044] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0045] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0046] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0047] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.

[0048] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.

[0049] The preparation of silicon-carbon negative electrode active materials usually adopts chemical vapor deposition technology. Specifically, nano-sized silicon (particle size less than 10nm) is evenly dispersed in the pores of porous carbon. The skeleton structure of porous carbon provides a physical buffer for silicon element, which helps to reduce the volume expansion of silicon element during charging and discharging, and improve the cycle stability of negative electrode active materials.

[0050] The pore size of porous carbon is a key factor affecting the performance of silicon-carbon anode. However, in order to reduce costs, commercially available porous carbon is mainly mesopores and macropores. However, when porous carbon with larger pore size is used as a substrate for silicon-carbon anode active materials, it tends to deposit and form silicon single substances with larger particle sizes, and even form silicon particles at the micron level. During the battery charging and discharging process, these silicon single substances with larger particle sizes will experience significant volume expansion, which may lead to problems such as particle rupture, material pulverization, and pole piece shedding of silicon-carbon anode active materials. These problems not only increase the consumption of electrolyte, but also may form an unstable solid electrolyte interface (SEI), thereby seriously affecting the cycle performance of the battery. In addition, the mechanical strength of porous carbon with larger pore size is obviously insufficient, and it cannot effectively buffer the huge volume change of silicon particles during the charging and discharging process, which leads to the destruction of the structure of porous carbon and the occurrence of material failure. Therefore, it is particularly important to develop a method for regulating the pore size of porous carbon to limit the deposition particle size of silicon single substances in order to improve the overall performance of silicon-carbon anode active materials and extend their cycle life.

[0051] In the first aspect of the present application, the present application provides a method for preparing a negative electrode active material, referring to Figure 1 , the method comprising:

[0052] S100, mixing metal nanoparticles and porous carbon to obtain a mixture.

[0053] In some embodiments, the mass of the metal nanoparticles is 0.1%-1% of the mass of the mixture. First, during the first carbon source deposition process, the metal nanoparticles act as the center of catalytic activity, promoting the decomposition of the carbon source gas on its surface, and at the same time, the metal nanoparticles provide nucleation points, making it easier for the carbon source gas to deposit carbon atoms on these nucleation points, thereby promoting the growth of carbon nanotubes and forming a uniform and dense carbon nanotube network; secondly, during the silicon source deposition stage, metal-silicon compounds or alloys are formed between the metal nanoparticles and the silicon element, and this interaction slows down the deposition rate of the silicon element, thereby controlling the growth of the size of the silicon element; at the same time, the carbon nanotubes formed in the pores of the porous carbon during the first carbon source deposition can block the macroporous structure of the porous carbon and reduce the pore size of the porous carbon. When the silicon source is subsequently deposited, the smaller pore size can limit the excessive deposition and excessive growth of the silicon element in the pores of the porous carbon.

[0054] Thus, the metal nanoparticles can both promote the growth of carbon nanotubes and restrict the growth of silicon, thereby achieving the regulation of the performance of the negative electrode active material. In the present application, the mass ratio of the metal nanoparticles is relatively low, and the above effect can be achieved without significantly increasing the cost.

[0055] As an example, the mass of the metal nanoparticles may be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.0% of the mass of the mixture.

[0056] In some embodiments, the porous carbon includes at least one of biomass-based porous carbon, resin-based porous carbon, and petroleum asphalt-based porous carbon. Therefore, different types of porous carbon have different pore structure characteristics, such as pore size, pore distribution, etc. Selecting porous carbon of suitable materials can provide a variety of growth spaces for the deposition of silicon and carbon nanotubes.

[0057] In some embodiments, the specific surface area of ​​the porous carbon is 500 m 2 / g-1000m 2 Therefore, by selecting porous carbon with a suitable specific surface area, it is possible to provide a suitable growth space for the deposition of silicon and carbon nanotubes while maintaining the stability of the porous carbon structure.

[0058] As an example, the specific surface area of ​​porous carbon can be 500 m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g or 1000m 2 / g.

[0059] In some embodiments, the metal nanoparticles include at least one of manganese, iron, cobalt, nickel, copper, and zinc. Thus, selecting metal nanoparticles of suitable materials can promote the decomposition of the carbon source gas during the deposition process and accelerate the growth of carbon nanotubes.

[0060] In some embodiments, the particle size of the metal nanoparticles is less than or equal to 10 nm. Therefore, selecting metal nanoparticles with a suitable particle size provides more active sites for subsequent catalytic reactions, thereby improving catalytic efficiency.

[0061] As an example, the particle size of the metal nanoparticles may be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, or 10 nm.

[0062] S200, performing a first carbon source deposition process on the mixed material to obtain a first material.

[0063] In some embodiments, the temperature of the mixture is raised to the deposition temperature of the first carbon source deposition process by the first temperature raising process. Thus, the mixture reaches the deposition temperature of the first carbon source deposition process in advance, which alleviates the problem of local overheating of the mixture during the first carbon source deposition process and provides a suitable growth environment for subsequent carbon nanotube deposition.

[0064] In some embodiments, the heating rate of the first heating treatment is 1° C. / min-10° C. / min. Thus, the slow heating rate helps to reduce the thermal stress of the mixture caused by the rapid temperature change, thereby reducing the risk of porous carbon cracking.

[0065] As an example, the heating rate of the first temperature heating treatment may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.

[0066] In some embodiments, the first temperature-raising treatment is performed in a first protective atmosphere, thereby preventing the mixed material from undergoing an oxidation reaction with oxygen in the air under a high temperature environment.

[0067] In some embodiments, the first protective atmosphere includes at least one of a hydrogen-argon mixed gas, a hydrogen-nitrogen mixed gas, nitrogen, and argon.

[0068] In some embodiments, when the first protective atmosphere contains hydrogen, the concentration of hydrogen in the first protective atmosphere is 1%-10%.

[0069] As an example, the concentration of hydrogen in the first protective atmosphere may be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0070] In some embodiments, the first carbon source deposition treatment satisfies at least one of the following conditions: the deposition temperature of the first carbon source deposition treatment is 1000°C-2000°C; the carbon source of the first carbon source deposition treatment includes at least one of acetylene, methane, and ethylene; the deposition time of the first carbon source deposition treatment is 0.1h-3h; the carbon source flow rate of the first carbon source deposition treatment is 0.1L / h-0.5L / h.

[0071] The first carbon source deposition is carried out at a high temperature of 1000℃-2000℃. The high temperature environment is conducive to the rapid decomposition of the carbon source gas and the rapid deposition of carbon nanotubes, and then the carbon nanotubes formed in the pores of the porous carbon can block the macropores of the porous carbon or reduce the pore size of the porous carbon. When the silicon source is deposited, the smaller pore size can limit the deposition and growth of silicon element in the pores of the porous carbon. At the same time, by selecting a suitable carbon source gas, the pore structure of different porous carbons can be matched; by controlling the deposition time of the carbon source, it is helpful to control the growth degree of the carbon nanotubes; by adjusting the carbon source flow rate, it is helpful to control the contact time between the carbon source gas and the metal nanoparticles, and then control the growth rate of the carbon nanotubes.

[0072] Therefore, selecting appropriate deposition temperature, carbon source, deposition time, and carbon source flow rate is conducive to the decomposition of the carbon source gas and the formation of carbon nanotubes.

[0073] As an example, the deposition temperature of the first carbon source deposition process may be 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, 1900°C, or 2000°C.

[0074] As an example, the deposition time of the first carbon source deposition process may be 0.1 h, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0075] As an example, the carbon source flow rate of the first carbon source deposition process may be 0.1 L / h, 0.2 L / h, 0.3 L / h, 0.4 L / h, or 0.5 L / h.

[0076] As an example, the first carbon source deposition treatment satisfies the following conditions at the same time: the deposition temperature of the first carbon source deposition treatment is 1000°C-2000°C; the carbon source of the first carbon source deposition treatment includes at least one of acetylene, methane, and ethylene; the deposition time of the first carbon source deposition treatment is 0.1h-3h; the carbon source flow rate of the first carbon source deposition treatment is 0.1L / h-0.5L / h.

[0077] S300, performing silicon source deposition processing on the first material to obtain a second material.

[0078] In some embodiments, the first temperature reduction process is performed to reduce the temperature of the first material to the deposition temperature of the silicon source deposition process, thereby providing a suitable growth environment for subsequent silicon single substance deposition.

[0079] In some embodiments, the cooling rate of the first cooling treatment is 1°C / min-10°C / min. Thus, a slow cooling rate helps to reduce significant deformation of the first material due to excessively fast cooling, thereby reducing the risk of the first material breaking.

[0080] As an example, the cooling rate of the first cooling treatment may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.

[0081] In some embodiments, the first temperature reduction treatment is performed in a second protective atmosphere.

[0082] In some embodiments, the second protective atmosphere includes at least one of a hydrogen-argon mixed gas, a hydrogen-nitrogen mixed gas, nitrogen, and argon.

[0083] In some embodiments, when the second protective atmosphere contains hydrogen, the concentration of hydrogen in the second protective atmosphere is 1%-10%.

[0084] As an example, the concentration of hydrogen in the second protective atmosphere may be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0085] In some embodiments, the silicon source deposition process satisfies at least one of the following conditions: the deposition temperature of the silicon source deposition process is 450°C-650°C; the silicon source of the silicon source deposition process includes at least one of silane, disilane, dichlorosilane, tetramethylsilane, and dimethyldichlorosilane; the deposition time of the silicon source deposition process is 0.5h-5h; the silicon source flow rate of the silicon source deposition process is 0.1L / h-0.5L / h.

[0086] Compared with the first carbon source deposition temperature, the silicon source deposition temperature is 450℃-650℃. The lower silicon source deposition temperature can slow down the deposition rate of silicon, thereby limiting the size of silicon ions to the nanometer range. At the same time, by selecting a suitable silicon source gas, the pore structure of different porous carbons can be matched; by controlling the deposition time of the silicon source, it is helpful to control the growth degree of silicon; by adjusting the flow rate of the silicon source, it is helpful to control the contact time between the silicon source gas and the metal nanoparticles, thereby controlling the growth rate of the silicon.

[0087] Therefore, choosing the appropriate deposition temperature, silicon source, deposition time, and silicon source flow rate will help control the size of the silicon element.

[0088] As an example, the deposition temperature of the silicon source deposition process may be 450°C, 500°C, 550°C, 600°C, or 650°C.

[0089] As an example, the deposition time of the silicon source deposition process may be 0.5 h, 1 h, 2 h, 3 h, 4 h or 5 h.

[0090] As an example, the silicon source flow rate of the silicon source deposition process may be 0.1 L / h, 0.2 L / h, 0.3 L / h, 0.4 L / h, or 0.5 L / h.

[0091] As an example, the silicon source deposition process satisfies the following conditions at the same time: the deposition temperature of the silicon source deposition process is 450°C-650°C; the silicon source of the silicon source deposition process includes at least one of silane, disilane, dichlorosilane, tetramethylsilane, and dimethyldichlorosilane; the deposition time of the silicon source deposition process is 0.5h-5h; the silicon source flow rate of the silicon source deposition process is 0.1L / h-0.5L / h.

[0092] S400, performing a second carbon source deposition process on the second material to obtain a negative electrode active material.

[0093] In some embodiments, the second temperature raising process is performed to raise the temperature of the second material to the deposition temperature of the second carbon source deposition process, thereby providing a suitable growth environment for the subsequent carbon coating layer deposition.

[0094] In some embodiments, the heating rate of the second heating treatment is 1° C. / min-10° C. / min.

[0095] As an example, the heating rate of the second temperature rising treatment may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.

[0096] In some embodiments, the second temperature increase treatment is performed in a third protective atmosphere.

[0097] In some embodiments, the third protective atmosphere includes at least one of a hydrogen-argon mixed gas, a hydrogen-nitrogen mixed gas, nitrogen, and argon.

[0098] In some embodiments, when the third protective atmosphere contains hydrogen, the concentration of hydrogen in the third protective atmosphere is 1%-10%.

[0099] As an example, the concentration of hydrogen in the third protective atmosphere may be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0100] In some embodiments, the second carbon source deposition treatment satisfies at least one of the following conditions: the deposition temperature of the second carbon source deposition treatment is 700°C-1000°C; the carbon source of the second carbon source deposition treatment includes at least one of acetylene, methane, and ethylene; the deposition time of the second carbon source deposition treatment is 0.1h-3h; the carbon source flow rate of the second carbon source deposition treatment is 0.1L / h-0.5L / h.

[0101] The second carbon source deposition is carried out at a temperature of 700℃-1000℃, which belongs to the secondary medium-temperature carbon deposition process. The porous carbon surface is constructed to form a carbon coating with elastic protection and high conductivity. The carbon coating can not only inhibit the volume expansion of silicon, but also improve the mechanical strength and electrochemical properties of the porous carbon, and alleviate the problem of silicon-carbon negative electrode active materials falling off due to silicon expansion during the cycle. At the same time, by controlling the deposition time of the carbon source, it is helpful to control the coating degree of the carbon coating layer and alleviate the excessive or insufficient deposition of the carbon coating layer; by adjusting the carbon source flow rate, it is helpful to control the growth rate of the carbon coating layer.

[0102] Therefore, selecting appropriate deposition temperature, carbon source, deposition time, and carbon source flow rate helps to control the coating degree of the carbon coating layer.

[0103] As an example, the deposition temperature of the second carbon source deposition process may be 700°C, 800°C, 900°C, or 1000°C.

[0104] As an example, the deposition time of the second carbon source deposition process is 0.5 h, 1 h, 2 h, 3 h, 4 h or 5 h.

[0105] As an example, the carbon source flow rate of the second carbon source deposition process is 0.1 L / h, 0.2 L / h, 0.3 L / h, 0.4 L / h or 0.5 L / h.

[0106] As an example, the second carbon source deposition treatment satisfies the following conditions at the same time: the deposition temperature of the second carbon source deposition treatment is 700°C-1000°C; the carbon source of the second carbon source deposition treatment includes at least one of acetylene, methane, and ethylene; the deposition time of the second carbon source deposition treatment is 0.1h-3h; the carbon source flow rate of the second carbon source deposition treatment is 0.1L / h-0.5L / h.

[0107] In summary, the present application introduces metal nanoparticles into the pores of large-aperture porous carbon. In the first high-temperature carbon deposition process, the metal nanoparticles are used as nucleation centers to promote the carbon source gas to form a network structure of single-walled or multi-walled carbon nanotubes in the pores or on the surface of the porous carbon. The formed carbon nanotube coating not only exhibits high crystallinity and hardness, but also has good conductivity and mechanical properties, while effectively blocking the large pores of the porous carbon, thereby reducing the pore size of the porous carbon; in the subsequent low-temperature silicon deposition stage, silicon element is deposited on the surface of the carbon nanotubes or in the smaller porous carbon pores, limiting the excessive growth of silicon element, and the low temperature environment also limits the excessive growth of silicon element; finally, in the second medium-temperature carbon deposition process, a carbon coating layer with elastic protection and high conductivity is formed on the surface of the porous carbon, and the carbon coating layer can not only inhibit the volume expansion of silicon, but also improve the mechanical strength and electrochemical properties of the porous carbon, thereby alleviating the problem of silicon-carbon negative electrode active materials falling off due to the expansion of silicon element during the cycle.

[0108] In a second aspect of the present application, the present application provides a negative electrode active material prepared by the above method, wherein the prepared negative electrode active material has high specific capacity, good cycle stability and high initial charge and discharge efficiency.

[0109] In the third aspect of the present application, the present application provides a battery, including a negative electrode sheet, the negative electrode sheet including a current collector, and a negative electrode active material layer located on at least one side of the current collector, the negative electrode active material layer including a negative electrode active material, and the negative electrode active material includes a negative electrode active material prepared by the aforementioned method, or the aforementioned negative electrode active material. Therefore, the battery of the present application has the advantages of high energy density, good cycle stability and good safety, and meets the needs of high-energy and long-life batteries.

[0110] In some embodiments, the current collector comprises copper foil.

[0111] In some embodiments, the negative electrode active material layer may further include a binder, for example, the binder includes at least one of sodium carboxymethyl cellulose, sodium alginate, and polyvinylidene fluoride.

[0112] In some embodiments, the negative electrode active material layer may further include a conductive agent. As an example, the conductive agent includes at least one of acetylene black, Ketjen black, and Super P carbon black.

[0113] In some embodiments, in the negative electrode active material layer, the mass ratio of the negative electrode active material to the binder is (6-9):(0.5-2). As an example, the mass ratio of the negative electrode active material to the binder includes but is not limited to 6:0.5, 6:1, 6:2, 7:0.5, 7:1, 7:2, 8:0.5, 8:1, 8:2, 9:0.5, 9:1, 9:2.

[0114] In some embodiments, in the negative electrode active material layer, the mass ratio of the negative electrode active material to the conductive agent is (6-9):(0.5-2). As an example, the mass ratio of the negative electrode active material to the conductive agent includes but is not limited to 6:0.5, 6:1, 6:2, 7:0.5, 7:1, 7:2, 8:0.5, 8:1, 8:2, 9:0.5, 9:1, 9:2.

[0115] In some embodiments, the negative electrode sheet can be prepared by the following method: the negative electrode active material, binder, and conductive agent prepared by the above method are formulated into a slurry, and the slurry is applied to the surface of at least one side of the current collector; after the slurry is dried, a negative electrode sheet is obtained.

[0116] In some embodiments, the slurry includes water.

[0117] In some embodiments, the drying temperature of the slurry is 60°C-120°C.

[0118] As an example, the drying temperature of the slurry may be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, or 120°C.

[0119] In some embodiments, the drying time of the slurry is 1 h to 20 h.

[0120] As an example, the drying time of the slurry may be 1 h, 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h or 20 h.

[0121] In some embodiments, the electrolyte includes a lithium salt and a non-aqueous solvent.

[0122] In some embodiments, the lithium salt includes at least one of LiPF6, LiBF4, and LiClO4.

[0123] In some embodiments, the non-aqueous solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, and diethyl carbonate.

[0124] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0125] Example 1

[0126] The preparation of the negative electrode active material comprises the following steps:

[0127] S100, taking 10 g of biomass porous carbon and 0.01 g of nano iron powder, mechanically mixing for 2 h to obtain a uniformly mixed mixture;

[0128] S200, the mixture is heated to 1000° C. at a rate of 5° C. / min in a hydrogen-argon mixed atmosphere (hydrogen concentration is 5%); then acetylene gas is introduced, and the gas flow rate of acetylene gas is 0.1 L / h. After deposition for 2 hours, material 1 (the first material) is obtained;

[0129] S300, changing to a hydrogen-argon mixed atmosphere (hydrogen concentration is 5%), cooling material 1 to 450° C. at a rate of 5° C. / min; then changing to silane gas, the gas flow rate of silane gas is 0.1 L / h, and after deposition for 3 hours, obtaining material 2 (second material);

[0130] S400, change to a hydrogen-argon mixed atmosphere (hydrogen concentration is 5%), and heat material 2 to 700°C at a rate of 5°C / min; then change to acetylene gas, and the gas flow rate of acetylene gas is 0.1L / h. After deposition for 1 hour, material 3 is obtained; finally, change to a hydrogen-argon mixed atmosphere (hydrogen concentration is 5%), and cool material 3 to room temperature to obtain the negative electrode active material.

[0131] Preparation of negative electrode

[0132] The negative electrode active material, conductive agent Super P carbon black, and binder carboxymethyl cellulose were added to a water solvent in a weight ratio of 8:1:1, and then a small amount of anhydrous ethanol was used as a grinding aid; a planetary ball mill was used to mill for 30 minutes at a speed of 200 rpm / h to prepare a negative electrode slurry; the negative electrode slurry was evenly coated on the copper current collector with a scraper thickness of 150 μm, and dried at 80°C under vacuum conditions for 12 hours to prepare a 12 mm negative electrode sheet.

[0133] Battery Assembly

[0134] Using lithium sheets as counter electrodes and reference electrodes, the positive electrode sheets, negative electrode sheets, electrolytes and separators were assembled into 2016 button cells in a glove box with oxygen and water content below 0.1 ppm; the separator was PP; the electrolyte was a LiPF6 solution with a LiPF6 concentration of 1 mol / L; the solvent was a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DMC) in a volume ratio of 1:1, and 10% fluoroethylene carbonate (FEC) and 1% vinyl carbonate (VC) were added.

[0135] The difference between Examples 2-6 and Example 1 lies in the different reaction parameters for preparing the negative electrode active materials. Specifically, the reaction parameters for preparing the negative electrode active materials of Examples 1-7 are shown in Table 1.

[0136] Table 1

[0137]

[0138]

[0139] Comparative Example 1

[0140] S100, taking 10 g of biomass porous carbon as material 1;

[0141] S200, material 1 is heated to 550°C at a rate of 5°C / min in a hydrogen-argon mixed atmosphere (hydrogen concentration is 5%); then silane gas is passed through, and the gas flow rate of silane gas is 0.2L / h. After deposition for 3h, material 2 is obtained;

[0142] S300, change to a hydrogen-argon mixed atmosphere (hydrogen concentration is 5%), and heat material 2 to 800°C at a rate of 5°C / min; then change to acetylene gas, and the gas flow rate of acetylene gas is 0.2L / h. After deposition for 2h, material 3 is obtained; finally, change to a hydrogen-argon mixed atmosphere (hydrogen concentration is 5%), and cool material 3 to room temperature to obtain the negative electrode active material.

[0143] Comparative Example 2

[0144] S100, taking 10 g of resin porous carbon as material 1;

[0145] S200, material 1 is heated to 550°C at a rate of 5°C / min in a hydrogen-argon mixed atmosphere (hydrogen concentration is 5%); then silane gas is passed through, and the gas flow rate of silane gas is 0.2L / h. After deposition for 3h, material 2 is obtained;

[0146] S300, change to a hydrogen-argon mixed atmosphere (hydrogen concentration is 5%), and heat material 2 to 800°C at a rate of 5°C / min; then change to methane gas, and the gas flow rate of methane gas is 0.2L / h. After deposition for 2h, material 3 is obtained; finally, change to a hydrogen-argon mixed atmosphere (hydrogen concentration is 5%), and cool material 3 to room temperature to obtain the negative electrode active material.

[0147] Performance Testing:

[0148] 1. Test the specific surface areas of materials 1, 2 and 3 in the preparation process of negative electrode active materials.

[0149] 2. The button cell was tested for electrochemical performance on a Xinwei battery testing system. The charge and discharge voltage range was 0V-2V, the current density was 0.2C, and 1C = 1000mA / g.

[0150] The above test results are shown in Table 2.

[0151] Table 2

[0152]

[0153] The first cycle charge and discharge curve and the first 10 cycle specific capacity curve of the button cell prepared using the negative electrode active material of Example 4 are shown in FIG. Figure 2 , Figure 3 shown.

[0154] The first cycle charge and discharge curve and the first 10 cycle specific capacity curve of the button battery prepared using the negative electrode active material of Comparative Example 1 are shown in FIG. Figure 4 , Figure 5 shown.

[0155] As shown in Table 2, according to the specific surface area data of Examples 1-7 and Comparative Examples 1-2, during the first high-temperature carbon deposition process, the deposited carbon nanotubes can effectively block the macropores of the porous carbon, thereby reducing the pore size of the porous carbon, thereby limiting the subsequent growth of silicon.

[0156] The size of the first-cycle charge capacity directly reflects the battery's lithium storage capacity. In Comparative Example 1-2, since the silicon source is directly deposited on the porous carbon, larger particles of silicon element will be formed on the surface of the porous carbon, thereby increasing the contact area between the silicon element and the electrolyte during battery operation. Therefore, more lithium ions are stored, which makes the first-cycle charge capacity of Comparative Example 1-2 higher.

[0157] However, the larger particles of silicon in comparative example 1-2 have significant volume expansion and contraction during the charge and discharge process, which aggravates the wear of the negative electrode active material, thereby accelerating the cycle decay of the battery performance. According to the charging capacity data after 10 cycles of Example 1-7 and Comparative example 1-2, the battery prepared in Example 1-7 has good cycle stability, which is related to the double-layer coating structure of carbon nanotubes and carbon coating layer used in the negative electrode active material in Example 1-7, which helps to buffer the volume expansion of silicon in the charge and discharge process.

[0158] According to the first effective coulomb efficiency data of Examples 1-7 and Comparative Examples 1-2, when the silicon element with larger particles in Comparative Examples 1-2 is charged for the first time, more electrolyte participates in the formation of the SEI film, resulting in a lower first effective coulomb efficiency than that of Examples 1-7. Therefore, the battery prepared in Examples 1-7 has better electrochemical performance.

[0159] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing a negative electrode active material, characterized in that: include: mixing metal nanoparticles and porous carbon to obtain a mixture; Performing a first carbon source deposition process on the mixed material to obtain a first material; Performing a silicon source deposition process on the first material to obtain a second material; The second material is subjected to a second carbon source deposition process to obtain a negative electrode active material.

2. The method according to claim 1, characterized in that The mass of the metal nanoparticles is 0.1%-1% of the mass of the mixed material.

3. The method according to claim 1 or 2, characterized in that: The porous carbon includes at least one of biomass-based porous carbon, resin-based porous carbon, and petroleum asphalt-based porous carbon; and / or, The specific surface area of ​​the porous carbon is 500 m 2 / g-1000m 2 / g.

4. The method according to claim 1 or 2, characterized in that: The metal nanoparticles include at least one of manganese, iron, cobalt, nickel, copper and zinc; and / or, The particle size of the metal nanoparticles is less than or equal to 10 nm.

5. The method according to claim 1, characterized in that The first carbon source deposition process satisfies at least one of the following conditions: The deposition temperature of the first carbon source deposition process is 1000°C-2000°C; The carbon source for the first carbon source deposition treatment includes at least one of acetylene, methane, and ethylene; The deposition time of the first carbon source deposition treatment is 0.1h-3h; The carbon source flow rate of the first carbon source deposition process is 0.1 L / h-0.5 L / h.

6. The method according to claim 1, characterized in that The silicon source deposition process satisfies at least one of the following conditions: The deposition temperature of the silicon source deposition process is 450°C-650°C; The silicon source for the silicon source deposition process comprises at least one of silane, disilane, dichlorosilane, tetramethylsilane, and dimethyldichlorosilane; The deposition time of the silicon source deposition process is 0.5h-5h; The silicon source flow rate of the silicon source deposition process is 0.1 L / h-0.5 L / h.

7. The method according to claim 1, characterized in that The second carbon source deposition process satisfies at least one of the following conditions: The deposition temperature of the second carbon source deposition process is 700°C-1000°C; The carbon source of the second carbon source deposition treatment includes at least one of acetylene, methane, and ethylene; The deposition time of the second carbon source deposition treatment is 0.1h-3h; The carbon source flow rate of the second carbon source deposition process is 0.1 L / h-0.5 L / h.

8. The method according to any one of claims 1 to 7, characterized in that: Performing a first temperature increase treatment to increase the temperature of the mixed material to the deposition temperature of the first carbon source deposition treatment; and / or, Performing a first temperature reduction process to reduce the temperature of the first material to a deposition temperature of the silicon source deposition process; and / or, Through a second temperature raising process, the temperature of the second material is raised to the deposition temperature of the second carbon source deposition process, The heating rates of the first heating treatment and the second heating treatment are independently 1°C / min-10°C / min; the cooling rate of the first cooling treatment is 1°C / min-10°C / min.

9. A negative electrode active material, characterized in that: The method is prepared by any one of claims 1 to 8.

10. A battery, characterized in that: The invention comprises a negative electrode sheet, wherein the negative electrode sheet comprises a current collector, and a negative electrode active material layer located on at least one side of the current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a negative electrode active material prepared by the method described in any one of claims 1 to 8, or a negative electrode active material described in claim 9.

Citation Information

Cited By

  • Silicon-carbon negative electrode material, preparation method thereof and battery

    CN119943923A